THE USE OF LOOSE PARTS MEDIA AS A STRATEGY FOR DEVELOPING EARLY CHILDHOOD CREATIVITY - Novitasari, Nurul (Al Hikmah Indonesian Journal of Early Childhood Islamic Education, 2024)
This study is based on the low level of creativity among early childhood children in expressing ideas and creating independently. This issue is evident when children appear confused and lack confidence when asked to create free-form works without examples from teachers. Based on data analysis from previous studies, the low level of creativity in children is caused by monotonous teaching methods and the use of less engaging media. Therefore, a learning medium capable of optimally stimulating children's creativity is needed, one of which is loose parts media. This study aims to develop early childhood creativity through the use of loose parts media by utilizing natural materials available in the surrounding environment for Group B students at RA Mambaul Ulum Jatirogo. The research adopts a qualitative approach with a descriptive qualitative design. It was conducted at RA Mambaul Ulum Jatirogo, with the research subjects being Group B students. Data collection methods used include interviews, observation, and documentation. The data analysis process includes data reduction, data presentation, and conclusion drawing. The results of the study are as follows: 1) The creativity development of RA Mambaul Ulum students increased by 70% compared to before using loose parts media. 2) The implementation of loose parts media was conducted from Monday to Thursday using materials provided by the teacher.